NALCN channelopathies: Distinguishing gain-of-function and loss-of-function mutations. (13th September 2016) - Bend, Eric G.; Si, Yue; Stevenson, David A.; Bayrak-Toydemir, Pinar; Newcomb, Tara M.; Jorgensen, Erik M.; Swoboda, Kathryn J.
Abstract : Objective: To perform genotype–phenotype analysis in an infant with congenital arthrogryposis due to a de novo missense mutation in the NALCN ion channel and explore the mechanism of pathogenicity using a Caenorhabditis elegans model. Methods: We performed whole-exome sequencing in a preterm neonate with congenital arthrogryposis and a severe life-threatening clinical course. We examined the mechanism of pathogenicity of the associated NALCN mutation by engineering the orthologous mutation into the nematode C elegans using CRISPR-Cas9. Results: We identified a de novo missense mutation in NALCN, c.1768C>T, in an infant with a severe neonatal lethal form of the recently characterized CLIFAHDD syndrome (congenital contractures of the limbs and face with hypotonia and developmental delay). We report novel phenotypic features including prolonged episodes of stimulus-sensitive sustained muscular contraction associated with life-threatening episodes of desaturation and autonomic instability, extending the severity of previously described phenotypes associated with mutations in NALCN . When engineered into the C elegans ortholog, this mutation results in a severe gain-of-function phenotype, with hypercontraction and uncoordinated movement. We engineered 6 additional CLIFAHDD syndrome mutations into C elegans and the mechanism of action could be divided into 2 categories: half phenocopied gain-of-function mutants and half phenocopied loss-of-function mutants. Conclusions: The clinical phenotype of our patient and electrophysiologic studies show sustained muscular contraction in response to transient sensory stimuli. In C elegans, this mutation causes neuronal hyperactivity via a gain-of-function NALCN ion channel. Testing human variants of NALCN in C elegans demonstrates that CLIFAHDD can be caused by dominant loss- or gain-of-function mutations in ion channel function.